Guidelines for a Digital Scientific Presentation : An Update - V Subramaniam Arun; Tulsi Subramaniam (Wolters Kluwer Medknow Publications, 2004)
With advances in the world of scientific and professional presentation, digital media can be used effectively to assist and enhance communication without losing sight of the objective. This article discusses the use of computers, computer programs and other computerized equipment to assist and enhance audiovisual presentations.